2009
DOI: 10.1093/eurjhf/hfp037
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol abuse and heart failure

Abstract: Alcoholic patients who consume .90 g of alcohol a day for .5 years are at risk of developing asymptomatic alcoholic cardiomyopathy (ACM). Those patients who continue to drink may become symptomatic and develop signs and symptoms of heart failure (HF). This distinct form of congestive HF is responsible for 21-36% of all cases of non-ischaemic dilated cardiomyopathy in Western Society. Without complete abstinence, the 4 year mortality for ACM is close to 50%. This short review summarizes the experimental and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
112
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(118 citation statements)
references
References 133 publications
(193 reference statements)
2
112
0
4
Order By: Relevance
“…These mechanisms include cell loss resulting from necrosis or apoptosis, mitochondrial and sarcoplasmic reticulum dysfunction, changes in isoforms of myofilament proteins, and defective intracellular calcium transport. 13 Limitations of this study should be highlighted. This is a cross-sectional study, and as such, it does not permit to obtain conclusive evidence on a causal relationship between ethanol intake and LV diastolic dysfunction, although the dose dependence of association and independence from other major confounders might suggest so.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…These mechanisms include cell loss resulting from necrosis or apoptosis, mitochondrial and sarcoplasmic reticulum dysfunction, changes in isoforms of myofilament proteins, and defective intracellular calcium transport. 13 Limitations of this study should be highlighted. This is a cross-sectional study, and as such, it does not permit to obtain conclusive evidence on a causal relationship between ethanol intake and LV diastolic dysfunction, although the dose dependence of association and independence from other major confounders might suggest so.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, moderate ethanol intake contributes to early cardiac functional changes in hypertensive patients without affecting LV structure, an effect that is possibly related to direct toxic effects of ethanol to cardiomyocyte function leading to myocardial stiffening. 13 It is well known that alcohol abuse is associated with increased prevalence of hypertension 30 and progressive impairment of LV systolic function, leading to dilated cardiomyopathy and congestive heart failure. 31 Previous studies conducted with conventional echocardiographic technique reported also an association between ethanol consumption and impaired LV diastolic properties in asymptomatic chronic alcoholics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 TdP is a form of polymorphic ventricular tachycardia associated with a prolonged QT interval (either congenital or acquired). QT prolongation is known to occur in AWS.…”
Section: Discussionmentioning
confidence: 99%